2020
DOI: 10.1111/tid.13387
|View full text |Cite
|
Sign up to set email alerts
|

Association between the kinetics of cytomegalovirus reactivation evaluated in terms of the area under the curve of cytomegalovirus antigenemia and invasive mold infection during the post‐engraftment phase after allogeneic hematopoietic stem cell transplantation

Abstract: Background: We evaluated the clinical impact of cytomegalovirus (CMV) reactivation calculated in terms of the area under the curve of CMV antigenemia (CMV-AUC) on the development of invasive mold infection (IMI) in the post-engraftment phase after allogeneic hematopoietic stem cell transplantation (HSCT). Methods: Among 394 consecutive patients who underwent their first allogeneic HSCT at our center between 2007 and 2018, 335 were included after excluding patients with a past history of invasive fungal disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
7
2
Order By: Relevance
“…In addition, CMV‐AUC might be a surrogate marker of immunosuppresion caused by GVHD and corticosteroid usage. In fact, our previous study showed that CMV‐AUC was associated with the development of invasive mold infection during the postengraftment phase after allogeneic HSCT 32 . Surprisingly, grades II–IV or III–IV acute GVHD were not related to NRM or OS in this study.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, CMV‐AUC might be a surrogate marker of immunosuppresion caused by GVHD and corticosteroid usage. In fact, our previous study showed that CMV‐AUC was associated with the development of invasive mold infection during the postengraftment phase after allogeneic HSCT 32 . Surprisingly, grades II–IV or III–IV acute GVHD were not related to NRM or OS in this study.…”
Section: Discussioncontrasting
confidence: 70%
“…32 Kimura et al reported that the area under the curve of CMV antigenemia was an independent factor associated with IFI development. 36 Martino et al J o u r n a l P r e -p r o o f reported 20 out of 37 patients with IFIs had preceding CMV infection. 41 Two studies demonstrated that CMV infection significantly increased the risk of IFI based on multivariable logistic regression.…”
Section: Study and Patient Characteristicsmentioning
confidence: 96%
“…A total of 18 studies were extracted for the systematic review. 16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Six articles were excluded from meta-analysis due to lack of HR. 32,34,36,38,41,45 Accordingly, 12 studies were included for meta-analysis of post-transplant CMV and IFIs.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations